(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This paper analyzes the quarantine cuisine food behavior of the participants during the COVID-19 pandemic and their personal physical, mental, and emotional well-being. Using the concurrent nested mixed method design, a survey was conducted among the 65 personnel of a private Higher Education Institution in Northern Mindanao, Philippines. Data from this survey were used to probe the personnel’s experiences using a semi-structured interview. The results showed a significant relationship between the budget for food, food storage, safety and sanitation, eating habits and the physical, mental, social, and emotional well-being. Results also revealed that there is an apparent increase of body weight during the pandemic by the participants and that they see meaning and purpose in life and feel that faith impacts many of their decisions. From the culinary and nutritional perspectives, this study emphasizes the need for personnel to be mindful of the importance of good nutrition, and quality preparation of quarantine cuisine especially during the time of pandemic.